STEM-PjBL Learning Model To Enhance Critical Thinking Skills of Students on Magnets, Electricity, and Technology - Hasanah Dewi Lestari; Yuli Rahmawati; Herlina Usman (Jurnal Penelitian Pendidikan IPA, 2024)
This study aims to enhance the critical thinking skills of fifth grade elementary school students on topics of magnet, electricity, and technology through the STEM-PjBL model. The study involved 20 students. The research design employed was classroom action research conducted in three cycles. Qualitative data analysis techniques were utilized. The analysis of students' critical thinking skills focused on five indicators: Identify Question at Issue, conceptual understanding, ideas connection, assumptions, and inferences, with five levels of achievement. The results showed an improvement in critical thinking skills, with 75% of students' responses at a very good level of critical thinking, 35% at the mastering level in cycles I and II, and 45% in cycle III, along with 35% at the competent level. Meanwhile, those at the developing level were 15% in cycles I and II, increasing to 20% in cycle III. The remainder was 5% at the emerging stage in cycle I and 10% in cycle II. There were 5% at the absent level in cycle I. Therefore, the STEM-PjBL model can be considered an effective approach for students to enhance their critical thinking skills in IPAS learning and to support their active engagement in the classroom.